The effect of audit committee characteristics and risk-taking among Islamic financial institutions in Bangladesh / Md. Mohidul Islam … [et al.] - Islam, Md. Mohidul; Bhuiyan, Abul Bashar; Md Kassim, Aza Azlina; Rasli, Salina (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The purpose of the study is to examine whether audit committee characteristics influence the risk taking of the Islamic financial institutions (IFIs) in Bangladesh. The study conductedd dynamic short panel data regarding annual report of quated14 IFIs in Bangladesh during the period 2013-2018. Particularly the study examined with first and second lag of dependent variables are applied under GMM model in Stata software. The findings revealed that the audit committee size is significant positive effect on risk taking and it also documented that accounting and financial expertise in AC is significant negative relationship with risk taking. However, other audit committee characteristics, such as, ACs ’ meeting, attendance, educational level, and owners ’ identity, are not covered in this measurement. Future studies could extend the analyses by including these and other personal characteristics of directors to provide additional useful insights to this line of literature.